Augmented Reality-assisted Picture Storybook: Media to Enhance Discipline Character of Primary School Students - Lubis, Azmil Hasan; Wangid, Muhammad Nur (Universitas Pendidikan Indonesia, 2019)
This research is intended to determine the effectiveness of Augmented Reality-assisted picture storybook in improving discipline character of primary school students. The population of this research was all fourth-grade students of primary schools in Sleman Regency, Special Region of Yogyakarta, Indonesia. The method used is an experimental research, while the sampling technique was cluster random sampling technique. The data collection technique was disciplinary character observation technique. Furthermore, the data were analysed using t-test technique. The results of this research indicated that the value of sig. t-test was 0.00 (<0.05). Thus, it can be concluded that Augmented Reality-assisted picture storybook media was considered effective in enhancing disciplinary characters of primary school students.